Factors Analyze about Willingness of Elderly to Stay in Elderly Folk Home - I Ketut Sudiana; Retno Indarwati; Diana Rachmania (Universitas Airlangga, 2009)
Introduction : Moving to the new house is not easy for the elderly, especially moving to the elderly folk home. A lot of elderly refuse to stay in the elderly folk home. Some conditions which make the elderly give their willingness to stay in the elderly hostels such as economic status, family condition, and self desire. But that factors are unclear until now. The aim of this study was to analyze factors related to willingness for elderly living in the elderly hostels.Method : Design used in this study was cross sectional. The population were all of the elderly live in elderly folk home Hargo Dedali Surabaya. Samples were taken using purposive sampling and there were 20 respondents. Data were collected using structured questionnaire and then analyzed using Spearman’s rho test and logistic regression test with level of significance α≤ 0.05.Result : Result showed that the dominant factor of willingness of elderly living in the eladerly folk home was self desire with level of significance ρ=0.02, followed by economic status (ρ=0.031) and than family condition (ρ=0.032).Conclusion : It can be concluded that self desire was the major factor related to willingness of elderly living in the elderly folk home. Discussion : Further studies should be appraising how far the motivation appear from the elderly until they decided to live in the elderly folk home.